Developing human capital by linking emotional intelligence with personal competencies in Indian business organizations - Kavita Singh (International Journal of Business Science & Applied Management (IJBSAM), 2010)
The concept of emotional intelligence has become so popular in the management literature that it has become imperative to understand and leverage it for the sake of enhancin g the capacity of human capital in organizations. As the pace of change is increasing and world of work is making ever greater demands on a person?s cognitive, emotional and physical resources, this particular set of abilities are becoming increasingly im portant. Since majority of the concerns in organization involve people in different roles, emotional intelligence must become a determining factor for their effective management. It has also been found that ultimately it is the emotional and personal compe tencies that we need to identify and measure if we want to be able to predict performance at workplace resulting in its effectiveness, thereby enhancing the worth of the human capital. In this scenario the competencies possessed by the people will have a b earing on the extent to which they can actualize their emotional intelligence. The current paper sets out to examine the relationship between the emotional intelligence of executives in Indian business organizations with their personal competencies. The re sult suggests that emotional intelligence is significantly related with the personal competencies of employees and the variables of personal competency namely, people success, system success and self success have a predictive relationship with emotional in telligence.
Keywords: 650; emotional intelligence; personal competencies; self success; people success; task success; system success